Preserving the Mucosa to the Maximum Possible Extent for Endoscopic Submucosal Dissection of Subcircumferential Superficial Esophageal Carcinoma - Masaya Uesato; Kentarou Murakami; Yoshihiro Nabeya; Kazunori Fugo; Hisahiro Matsubara (Gastroenterology Research and Practice)
Aim. To show our unique strategy of endoscopic submucosal dissection (ESD) for esophageal squamous cell carcinoma larger than the subcircumference. Methods. From April 2011, we used a mucosal preservation method called the log bridge (LB) method for the lesion larger than the subcircumference. The patients in whom the circumference of the mucosal defect was 5/6 to <1 were classified into the LB group; those who underwent whole circumferential ESD were classified into the non-LB group. The data were collected retrospectively and were compared between the two groups. Results. Eighteen patients into the LB group and 7 into the non-LB group were classified. The median number of endoscopic balloon dilation sessions after ESD in the LB group tended to be lower than that in the non-LB group. The mean period until complete epithelialization after ESD was significantly shorter in the LB group. The rates of curative resection were 100% (7/7) in the non-LB group and 61.1% (11/18) in the LB group. However, there was no local recurrence in either group for approximately two years. Conclusion. In cases involving subcircumferential esophageal lesions, the LB method is useful for achieving rapid healing and might be related to a reduced degree of esophageal stricture.